Penerapan Manajemen Peserta Didik di Sekolah Dasar Negeri 1 Tlanak Kabupaten Lamongan - Mar’atus Sholikah, Rizka; Zaynul Alim, Moh.; Sebastian Putra, Januar (JOURNAL OF EDUCATION FOR ALL, 2023)
One of the efforts to increase the achievement and quality of students in elementary schools is in Student Management. The benchmark for successful achievement in educational institutions is students who are managed properly and well. Management of students is an effort to regulate students starting from students entering school until they graduate from school. The activities of managing these students consist of planning, coaching, evaluation and transfer. The research in this article has the goal of knowing the management of students at Tlanak 1 Elementary School in Lamongan Regency. The method used is a qualitative research method by applying an approach that focuses on phenomena. This data acquisition was obtained from the results of observations, interviews, and documentation studies. The results of this study found the conclusion that Tlanak 1 Elementary School in Lamongan Regency was founded for 23 years to create students with management concepts who have superior insight and have good character education. Student management activities at Tlanak 1 Public Elementary School consist of planning, coaching, evaluating and transferring students.